2008
DOI: 10.1111/j.1582-4934.2008.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of aquaporins and regulation of secretory vesicle volume in cell secretion

Abstract: In exocrine glands, secretory proteins synthesized in the rough endoplasmic reticulum (RER) exhibit vectorial transport from ER through a succession of membrane-bounded components such as Golgi complex, condensing vacuoles and secretory granules. The secretory granules migrate to particular locations within the cell close to the apical membrane prior to the release of their contents into the acinar lumen. Currently, to release intragranular contents, secretory granules have been demonstrated to transiently doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…The proteins originating from Igh-4 and Aqp8 up-regulate phagocytosis and the migration of leukemia, respectively [26,27]. Elastases originating from Ela3 and Ela1 attach to microorganisms and foreign substances [28].…”
Section: Figmentioning
confidence: 99%
“…The proteins originating from Igh-4 and Aqp8 up-regulate phagocytosis and the migration of leukemia, respectively [26,27]. Elastases originating from Ela3 and Ela1 attach to microorganisms and foreign substances [28].…”
Section: Figmentioning
confidence: 99%
“…AQPs represent constitutive elements of the plasma membrane in most secretory cell types of exocrine glands [19][20][21][22][23][24][25] . Recently, their presence has been demonstrated in secretory granules and vesicles, indicating an involvement in volume regulation of these structures 26) . In the salivary glands, AQP5 is probably involved in providing for an appropriate amount of fluid to be secreted 26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, their presence has been demonstrated in secretory granules and vesicles, indicating an involvement in volume regulation of these structures 26) . In the salivary glands, AQP5 is probably involved in providing for an appropriate amount of fluid to be secreted 26,27) . In particular, in rat salivary glands, AQP5 is highly expressed in the apical plasma membrane of serous acinar cells, in the secretory canaliculi and in the intercalated duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, their presence has been demonstrated in secretory granules and vesicles, indicating an involvement in volume regulation of these structures [15]. Recent research on humans and laboratory mammals, aimed at identifying aquaporins and aquaglyceroporins in the digestive system, has demonstrated that AQP water channels are involved in the physiologic processes of digestion and absorption of the ingesta [16,17].…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…In the salivary glands, AQP5 is probably involved in providing for an appropriate amount of fluid to be secreted [15,30]. In particular, in rat salivary glands, AQP5 is highly expressed in the apical plasma membrane of serous acinar cells, in the secretory canaliculi and in the intercalated duct cells.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%